RIGHTS OWNERSHIP TO CERTIFIED LAND CONFRONTED WITH THE CUSTOMARY LAW IN THE LEGAL SYSTEM IN INDONESIA - Saim - Aksnudin (SAMPURASUN, 2018)
In the national development the role of land for the fulfillment of various purposes will increase, either as a place to live or for business activities. In relation to that will also increase the need for support in the form of guarantee of legal certainty in the field of land. The result of the research is the conception of the state of Indonesia is a state law, which contains the meaning in the administration of government and the state based on the law, the protection of the law is a universal concept of the rule of law. The legal certainty on land rights as intended by the UUPA encompasses three things, namely the certainty of the object of land rights, certainty on the subject of land rights and certainty about the status of landrights. Legal conception of land title certificate is a proof that issued by authorized legal institution, containing juridical data and physical data which isused as evidence of ownership of land rights in order to provide assurance of legal certainty and certainty of rights to a plot of land owned or possessed by a person or legal entity. With the certificate of rights, it is expected that the juridical can guarantee the legal certainty and the right by the state for the holder of the right to the land. This country's guarantee is granted to the owner or the holder of the certificate may be granted because the land is already registered in the state land administration system.